Pengaruh Profitabilitas Likuiditas dan Ukuran Perusahaan terhadap Nilai Perusahaan - Femelia Yovita Bita; Sri Hermuningsih; Alfiatul Maulida (Jurnal Syntax Transformation, 2021)
This study aims to analyze the effect of profitability, liquidity, and firm size on firm value. This research includes descriptive statistical research, the object of this research is property and real estate companies listed on the Indonesia Stock Exchange (BEI) 2015-2019. This study used a purposive sampling method with several specified criteria, and the number of sample as many as 15 companies, and obtained for five years from the annual financial reports, so that the total sample of companies is 75 companies. The type of data used in this study is secondary data, where data obtained from ready-made forms have been collected and processed by other parties in the form of samples of the company's annual financial statements. To determine the effect of the independent variable on the dependent variable, the analytical method used is the descriptive statistical test, t test, f test, and analysis of the coefficient of determination using the SPSS program. The results of this study indicate that profitability has a positive and significant effect on firm value, liquidity has a positive and significant effect on firm value and firm size has a positive and significant effect on firm value.